2018
DOI: 10.1038/s41598-018-32280-x
|View full text |Cite
|
Sign up to set email alerts
|

Copper-to-copper direct bonding on highly (111)-oriented nanotwinned copper in no-vacuum ambient

Abstract: A vacuum-free Cu-to-Cu direct bonding by using (111)-oriented and nanotwinned Cu has been achieved. A fast bonding process occurs in 5 min under a temperature gradient between 450 and 100 °C. It is verified by grain growth across the bonded interface. To investigate the grain growth behavior, further annealing in the temperature gradient, as well as in a reversed temperature gradient, was performed. They showed similar recrystallization behavior with de-twinning. To analyze the de-twinning, we recall the class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…The distribution of grains is also presented in the enlarged images of the bonding interfaces (blue squares in Figure 4 c,d). Some triple junctions [ 42 , 43 ] were detected (blue arrows in Figure 4 c). These triple junctions led to a zig-zag bonding interface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of grains is also presented in the enlarged images of the bonding interfaces (blue squares in Figure 4 c,d). Some triple junctions [ 42 , 43 ] were detected (blue arrows in Figure 4 c). These triple junctions led to a zig-zag bonding interface.…”
Section: Resultsmentioning
confidence: 99%
“…Some Cu grains recrystallized, and further little grains grew at the center of the bonding interface. Several zig-zag cracks propagated along the fine grains in Figure 6 c. In contrast, the cracks are straighter in Figure 6 d because the grains did not recrystallize and grow across the weak grain boundaries to form triple junctions at the bonding interface [ 42 , 43 ]. This difference was caused by the microstructure of as-fabricated Cu–Cu bumps in Figure 4 c,d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, grain growth took place across the bonding interfaces at temperatures of 300 °C/100 °C (Figure 3c). The grown grains in the pillar bump side began merging with the lower nt-Cu columnar grains in the thin film side [21]. Finally, most nt-Cu columnar grains in the lower thin film side were consumed.…”
Section: Resultsmentioning
confidence: 99%
“…Much research on low temperature Cu-to-Cu bonding has been reported [4][5][6][7][8][9][10][11][12][13][14]. The research includes coverage of surface activated bonding [4], passivation using a self-assembled monolayer [5], wet cleaning [6,7], metal passivation with Pd, Mg, Ag, or Au [8][9][10][11], Cu (111) crystal plane studies [12], Cu/SiO 2 hybrid bonding [3,13], and Cu/polymer hybrid bonding [14]. So far, the direct bonding interconnect (DBI) technique by Ziptronix [13] has been considered the most adoptable Cu bonding process in mass production.…”
Section: Introductionmentioning
confidence: 99%